The decision-making process in public healthcare entities – identification of the decision-making process type - Szymaniec-Mlicka Karolina (Management, 2017)
The decisions made in the organization determine its success, therefore, conducting studies in the scope of decision-making seems important both for theory and practice. The aim of the studies was to identify the type of decision-making process in public medical entities with the use of typology developed by P. Nutt. For this purpose we used qualitative methods. Interviews with 8 directors of hospitals were conducted and the reconstruction was made on the basis of the decision-making process, which enabled the assignment of the model of decision-making process to the organization. The research indicated that four organizations use the historical decision-making model, three organizations represent the model of generating solutions, and one organization uses the model of available solutions.